THE INFLUENCE OF CAREGIVER-PATIENT RELATIONSHIP QUALITY AND CAREGIVER BURDEN ON LONG-TERM CARE USE IN SINGAPORE. (11th November 2018) - Chong, W; Ho, R; Luo, N; Koh, G
Abstract: As the fastest ageing Asian nation, multi-ethnic Singapore expects increasing demand for formal and informal long-term care services (LTCS). However, when compared to Western contexts, the current formal LTCS utilization is relatively low, while the informal LTCS utilization relatively high. Previous research has uncovered patient factors for LTCS use. To improve service planning and design, this study aims to elucidate the caregiver factors that influence LTCS use in Singapore. A 12-month prospective cohort survey of caregiver-stroke patient dyads with data collection at baseline, 3-month, and 12-month was conducted. Eligible patients and their informal caregivers (family or friend) were recruited from all five public tertiary hospitals in Singapore between December 2010 and September 2013, at the point of hospital admission. 638 patients who were above 40 years old, and who were diagnosed with a recent stroke event, and their 383 caregivers, responded to all three waves of this study. Logistic regressions revealed that better wave-1 caregiver-patient relationship quality has 63.2% and 76.8% higher odds of predicting wave-2 and wave-3 informal care use than non-use, respectively. Better wave-1 caregiver-patient relationship quality has 25.9% higher odds of predicting wave-2 concurrent use of both formal and informal LTCS, as compared to use of informal LTCS only. Higher wave-1 caregiver burden has 4.1% higher odds of predicting wave-2 formal care use than non-use. Formal LTCS use complements rather than substitute informal LTCS use. Services aimed at improving caregiver-patient relationship quality and identifying burdened caregivers prior to an older person's functional decline should be considered.